A Review on Fuel Cell as Advanced Power Source - S K Kamarudin; W R Daud; M S Ayub; A W Mohammad; S E Iyuke (ASEAN Journal of Chemical Engineering, 2002)
Fuel cells are making headlines across the globe in almost all arenas of power production. While the technology for these electrochemical power plants was invented around 1839 and has been in use for nearly 150 years, it is only recently that fuel cells have gained popular recognition and reckoned for serious consideration as a power zone for the future. Despite their relatively new arrival on the popular scene, fuel cells have already found their way into pre-commercial testing in domestic, commercial, industrial and mobile applications. Fuel cells convert chemical energy of a fuel gas directly into electrical work, and are efficient and environmentally clean, since no combustion is involved. Fuel cells are presently under development for a variety of generation application in response to the critical need for a cleaner energy technology. The use of fuel cell systems has been strongly promoted in Japan and the United States for medium-scale co-generation plants. Nowadays, this interest has been extended to the smaller scale, in particular at the residential area level. All fuel cells currently being developed for near term use in electric vehicles require hydrogen as a fuel. At the same time, increased interest has arisen for the application of fuel cell systems to automotive propulsion, although there is no clear option on the direct use of hydrogen stored on board or the installation of hydrogen plant on board as of this time. This paper outlines the acute global population growth and the growing need and use of energy and its component as well as its environmental impact. In particular, this paper reviews the existing or emerging fuel cells technologies, limitations, and their benefits in connection with energy, environment and sustainable development relationship. In addition, this paper also explores fuel sources and the various types of fuel cells as well as their applications.